Traditional medicinal plants used in the treatment of diabetes: Ethnobotanical and ethnopharmacological studies and mechanisms of action - Messaoud Belmouhoub; Mustapha Tacherfiout; Farid Boukhalfa; Yazid Khaled Khodja; Mostapha Bachir-Bey (International Journal of Plant Based Pharmaceuticals, 2022)
The use of medicinal plants for the prevention and treatment of several diseases, particularly diabetes, remains the remedy and the sustainable source for many diseases. This survey was conducted out in Bejaia province in the center of Algeria to invent the main plants used in folk medicine to treat diabetes mellitus, their availability in this region, and the mode of their use. This study was carried out in 2019 in several municipalities of the study area. Ethnobotanical information was obtained using a questionnaire through direct interviews with 323 people with diabetes. Among people with diabetes interviewed, 82% present type 2 diabetes, from which more than 60% of them use medicinal plants against 36.84% only in type 1 diabetics. Diabetes affected age groups differently; the age range most affected was 61-80 years (43.96%). A total of 43 plant species belonging to 25 families were identified and listed in this study. The most frequent species used by patients are Artemisia herba-alba (34.42%), Olea europaea (13.66%), and Ajuga iva (11.47%). The part of the plant used depends on the plant; the aerial part was the more used (40.9%), followed by leaves (25%) and fruits (13.63%). The other parts, such as seed, root, flower, bark, bulb, epicarp, and rhizome, were used with low frequencies. It was also interesting to indicate that decoction and infusion were the systematic preparation methods compared to others (maceration, cooking with food, and fresh). The present study clearly showed that phytotherapy is widely adopted by center Algerian society, and there is a huge diversity of medicinal plants used for the complementary treatment of diabetes. Moreover, this investigation provides researchers with important information that can be exploited to develop anti-diabetic remedies.